Bacteriological Profile and Antibiotic Susceptibility of Neonatal Sepsis Cases in the Neonatal Intensive Care Unit of a Tertiary Hospital in Türkiye - Bayram Ali Dorum; Şefika Elmas Bozdemir; Bensu Zadeoğlu Kral; Ayten Erdoğan; Salih Çağrı Çakır (MDPI AG, 2024)
Objective: We aimed to determine the demographic data, mortality, and morbidity of early- and late-neonatal sepsis cases, the etiologic agents in these cases, and the antibiotic susceptibility of these agents. Methods: This study was conducted retrospectively in a tertiary neonatal intensive care unit (NICU). The demographic, clinical, and laboratory data of newborns diagnosed with culture-proven sepsis within 24 months were evaluated. Results: Two hundred and eleven culture data points belonging to 197 infants were evaluated. Forty percent of the infants had a history of premature birth. The most common clinical findings were respiratory distress and feeding intolerance. Coagulase-negative staphylococci (CoNS) were detected most frequently as early- and late-sepsis agents. The most common Gram-negative bacteria detected as late-sepsis agents were Klebsiella spp. and Escherichia coli (E. coli). The overall mortality rate was 10%. Conclusions: Neonatal sepsis continues to have high mortality rates in tertiary NICUs. CoNS was the most common agent, highlighting the importance of developing and maintaining personnel training and handwashing practices. It will be important to consider the resistance rates of Klebsiella spp., the most common Gram-negative agent in late-onset sepsis (LOS) cases, to commonly used antibiotics in empirical treatments.